Hosting International Events and Promoting South Korean Identity Discourses: Continuities and Discontinuities. Issue 18 (11th December 2016) - Park, Kyoungho; Ok, Gwang; Merkel, Udo
Abstract: More than six decades after the end of the Korean War (1950–53), the Democratic People's Republic of Korea (DPRK) and the Republic of Korea (ROK) continue to face each other across the highly fortified Demilitarized Zone (DMZ) along the 38th parallel on the Korean peninsula. Both Korean governments continue to maintain and reinforce a pan-Korean identity amongst its respective populations. At the same time, both states need to provide its respective citizens with distinct national identities, which obviously requires a politically difficult and highly delicate balancing act. The focus of this paper is on the dominant identity discourses in South Korea. These have been observed, interpreted and analyzed in five international events and festivals that the South hosted over the last three decades: the 1988 Seoul Olympics, the 2002 Soccer World Cup (co-hosted with Japan), the Busan Asian Games in the same year, the 2011 Daegu World Athletic Championships and the 2014 Incheon Asian Games. All these events offered a distinctive nationalist flavour, celebrated tradition and modernity, and emphasized South Korea's rapid 20th century development and achievements, but also served as a reminder of the ethnic homogeneity of the divided Korean people and the unjust political division of the Korean peninsula.